2004
DOI: 10.1177/1045389x04042799
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Performance of the Smart Wing Control Effectors

Abstract: This paper presents and discusses the wind tunnel results obtained during Phase 1 and Phase 2 of the Smart Wing program. A series of four tests was conducted, two in each phase. The purpose of the tests was to evaluate the performance of smart material based control effectors in representative aerodynamic environments. In Phase 1, wing twist using a Shape Memory Alloy (SMA) torque tube and smoothly contoured trailing edge surfaces enabled by SMA wires were evaluated on a semi-span, 16% scale model of a typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Airfoils with conformal control surfaces that vary smoothly over the chord of the airfoil have been shown to have an aerodynamic advantage over airfoils with conventional, articulated ailerons [4]. For airfoil profiles Reynold's numbers in the 10 5 to 10 6 range, typical of the range for a small RC aircraft to larger UAVs, smoothly-varying the surface of the airfoil can positively influence several boundary layer features.…”
Section: Introductionmentioning
confidence: 98%
“…Airfoils with conformal control surfaces that vary smoothly over the chord of the airfoil have been shown to have an aerodynamic advantage over airfoils with conventional, articulated ailerons [4]. For airfoil profiles Reynold's numbers in the 10 5 to 10 6 range, typical of the range for a small RC aircraft to larger UAVs, smoothly-varying the surface of the airfoil can positively influence several boundary layer features.…”
Section: Introductionmentioning
confidence: 98%
“…In general, morphing aircraft is developed to increase vehicle performance by changing their external shapes during flight. 1 Morphing on a larger scale that involves significant changes in the camber, 2-4 wing span, [5][6][7] twist, 8,9 or sweep 10,11 has been profoundly investigated since the early 90's with NASA's Morphing Project. 12 A recent review on morphing aircraft, focusing on structural active morphing concepts, can be found in Barbarino.…”
Section: Introductionmentioning
confidence: 99%
“…These design solutions can be successfully used to control aircraft but they can have significant deficiencies with regard to aerodynamic performance, mass penalties, and complexity. There have been a number of shape-adaptive airfoil demonstrators in recent years that have attempted to address these problems [1][2][3][4][5][6][7]. The Intelligent Responsive Composite Structures (IRCS) program at the University of Bristol was initiated to investigate the design of adaptive structures using bistable composites as a means of providing aerodynamic control [8][9][10].…”
Section: Introductionmentioning
confidence: 99%